Pengaruh Fasilitas dan Kualitas Pelayanan terhadap Kepuasan Konsumen di SPBU Pertamina 14.201.180 Jl. Aksara, Satria Barat, Medan Perjuangan - Hermika Pinem; Arsyrah Fitri; Monika Ayu Lumbantoruan; Riski Lainatus Sifa; Ivo Selvia Agusti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of facilities and service quality on customer satisfaction at Pertamina gas station Jl. Aksara, Satria Barat, Medan Perjuangan. A quantitative method using multiple linear regression was employed, with data collected through questionnaires from 30 respondents using accidental sampling. The partial test (t-test) results show that service quality has a positive and significant effect on customer satisfaction, while facilities do not show a significant individual effect. However, simultaneously (F-test), both independent variables significantly and positively influence customer satisfaction. The coefficient of determination (R²) of 60.9% indicates that customer satisfaction can be explained by the variables of facilities and service quality. This research provides recommendations for gas station management to continuously improve service quality to maintain customer satisfaction.